From Physical Literacy to Human Flourishing: A Philosophical Literature Review of Modern Physical Education Paradigms - Agustin Sastrawan Harahap; Zen Fadly; Sinung Nugroho; Hardodi Sihombing; Agung Sunarno; Nurkadri Nurkadri; Budi Valianto (Joska: Jurnal Isori Kampar, 2026)
Objectives: This systematic philosophical literature review examines the conceptual evolution from physical literacy frameworks to human flourishing paradigms in contemporary physical education (PE), analyzing how philosophical foundations have shaped modern pedagogical approaches and their implications for holistic human development. Methods: Following PRISMA guidelines, a systematic search was conducted across Web of Science, Scopus, PubMed, ERIC, and SPORTDiscus databases (January 2010–August 2025). Search terms combined physical literacy, physical education, human flourishing, eudaimonia, well-being, and philosophical paradigms. Inclusion criteria encompassed peer-reviewed philosophical, theoretical, and empirical studies examining PE paradigms through philosophical lenses. Two independent reviewers screened 2,847 records, with 56 studies meeting full eligibility criteria for qualitative synthesis. Results: A paradigmatic shift was identified from narrow skill-based competencies toward comprehensive human flourishing, with physical literacy serving as foundational but not sufficient for optimal human development. Integration challenges included conceptual ambiguity, measurement difficulties, and implementation barriers in diverse educational contexts. Conclusion: Contemporary PE paradigms demonstrate philosophical convergence toward holistic human development models, transcending traditional dualistic mind-body separations. Physical literacy emerges as a necessary foundation for human flourishing but requires integration with cognitive, affective, and social domains.